Estudio de factibilidad para la producción de queso parmesano en la Asociación Sierra Nevada de la comunidad de Cumbijín. - Amaya Gavilanes, Alisson Melissa (2022)
This research study arose due to a large amount of raw material available in the community, which is intended to add value to the raw milk collection center of the "Sierra Nevada" Association since it is responsible for collecting and subsequently cooling about 7,000 liters daily. For this reason, this feasibility study was conducted to determine the viability of the production and marketing of Parmesan cheese and thus diversify the source of economic income of the organization, field research was carried out by visiting the plant for diagnosis and data collection. The market study showed that the product has a 68% acceptance rate, and the unsatisfied demand for the product was identified. Next, the productive capacity of the microenterprise was determined through the unsatisfied demand, with the intention of covering 52% in the first year, and the technical study detailed the necessary requirements for the production of Parmesan cheese. Subsequently, the administrative study determined that the ‘Sierra Nevada’ Association operates under the legal and organizational framework of the SEPS (Superintendence of Popular and Solidarity Economy), establishing itself as a microenterprise whose main function is the collection of raw milk. Finally, the financial study calculated the main indicators, and as a result, favorable figures were obtained for the viability of the project, the NPV value was ($ 142.067,99) and an IRR equivalent to 30%.